2019
DOI: 10.21470/1678-9741-2018-0299
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Major Adverse Events after Surgical Closure of Ventricular Septal Defect in Patients Less than 1 Year of Age: A Single-Center Retrospective

Abstract: Objective To reveal the risk factors that can lead to a complicated course and an increased morbidity in patients < 1 year old after surgical ventricular septal defect (VSD) closure. Methods We reviewed a consecutive series of patients who were admitted to our institution for surgical VSD closure who were under one year of age, between 2015 and 2018. Mechanical ventilation (MV) time > 24 hours, intensive care unit (ICU) stay longer than three days, and hospital stay lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
1
25
0
2
Order By: Relevance
“…Fifth, variables of patient-specific factors such as height, weightfor-age z-score reflect preoperative growth, nutritional status, and perfusion of systemic circulation, so a deficiency in height and weight indicates a high risk of death and other postoperative adverse events (35,36). Finally, the variable of LVPW reflects the status of pre-operation left ventricular remodeling, but this variable was discovered also to be related to other factors such as diagnosis group (LVPW was higher in the group without VSD), age (to a certain extent reflecting the course of disease for congenital malformation), and severe PH (LVPW was greater in the non-severe PH group than in the severe PH group) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, variables of patient-specific factors such as height, weightfor-age z-score reflect preoperative growth, nutritional status, and perfusion of systemic circulation, so a deficiency in height and weight indicates a high risk of death and other postoperative adverse events (35,36). Finally, the variable of LVPW reflects the status of pre-operation left ventricular remodeling, but this variable was discovered also to be related to other factors such as diagnosis group (LVPW was higher in the group without VSD), age (to a certain extent reflecting the course of disease for congenital malformation), and severe PH (LVPW was greater in the non-severe PH group than in the severe PH group) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, both methods carry a potential risk of complete atrioventricular block (cAVB). Studies show cAVB occurs at a rate of 0.1-6.8% after interventional VSD closure [4][5][6][7][8][9][10][11][12][13] and < 2% after surgical VSD closure [14,15]. Surgical closure can be considered for the majority of patients but disadvantages include the use of general anesthesia, sternotomy, and extracorporeal circulatory support, which results in longer recovery and hospital time [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al reported that the incidence of MAE was 5.3% and Schipper et al reported the incidence of MAE was 2.9% in their respective studies (1,3) . Our study focused on the population under the age of one year and found that the incidence of MAE was 5.4% (7) . However, we observed that the incidence of MAO was quite low in the patient population after the age of one year.…”
Section: Discussionmentioning
confidence: 96%